Reconsidering Brechtian elements in process drama - Özgehan UŞTUK (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi, 2015)
It is known that process drama is parallel to non-Aristotelian structure of Brecht’s epic theatre in certain ways. Techniques and structure as the elements of these two notions (O’Neill’s process drama and Brecht’s epic theatre) resemble to each other not only by the usage and also by the relationship between the process and the participants as well. Brecht intended to engage actively with the audience and makes them engage with the play critically; similarly in process drama structures, participants are actively engaged with the material and the theme of the work. Moreover, in process drama, participants are assigned as meaning-makers throughout the process since they actively shouldered the role of writer, director, actor/actress and the audience. This quality lets them engage with the process in ways that are not only aesthetic but also critical and purposeful. Thus, there are also some elements that Brechtian plays and O'Neill's structures may share but they are included with different intentions. Taking all the similarities and differences that can be referred from texts into consideration, it can be suggested that further discussion is needed to reveal the dichotomy. This paper intends to build a direct link between drama in education and theatre and to explain this link from a structural point of view by comparing and contrasting examples from plays of Brecht and process drama sessions of O'Neill